PERBEDAAN PENDAMPINGAN SUAMI DAN METODE TAPPING TERHADAP PENURUNAN TINGKAT KECEMASAN DAN INTENSITAS NYERI PADA PERSALINAN NORMAL - Munjiati Munjiati; Dina Indrati DS Indrati DS; Herry Prasetyo (STIKES BHAMADA SLAWI, 2016)
Background: husband mentoring and methods tapping in the intra-partum period can be used as an alternative methods during delivery Purpose: the study aimedtodetermine the effecthusbandmentoringandmethodstappingtheintra-partumperiodtodecreasethe level ofanxietyandpainintensityinnormal labor. Method: the research method wasquasi experimentwith non equivalent control group pre test and post test. The populationwas motherswithnormal deliveriesinthe maternity hospitalin the field of Community Health CenterBaturaden Banyumas.The sample sizewas30women.Data collectionwas donebefore and afterassistingwith thetappingmethod, usingobservation sheetmeasurementof anxietyandpain intensityscale. Results: the findings showed that therearesignificantdifferences inmeananxietyandpainin the first stage of intrapartumbeforeandafter theintervention periodin the intervention group, with averystrongcorrelationvaluesare0.853and0.764. The averagevalue ofthe significance ofanxietylevel in the intervention groupwas0.000<0.05 andthe averagevalue ofthe significance ofreduction in pain intensitywas0.001<0.05. Meanwhile, the control group, the level of significance0.005<0.05 for an averageof anxietybeforeandaftercounseling, butnottoa categoryaverage ofchildbirthpainfirst stageis0.635<0.05. Conclusion: tappingmethodassistance is verymeaningfultoreducepainandanxietyin the mothergave birth tothe first stage of intrapartum.